Noun Phrase Errors Made by Students in SMAN 1 Rupat Utara - Poppyosa Poppyosa; Dian Safitri (Journal of English Language Teaching, 2023)
This study aimed to find out the noun phrase errors and the dominant element errors, including determiner, pre-modifier, head, and post-modifier. This study's population consisted of students in grade eleven at SMAN I, Rupat Utara. The sample was taken using the purposive random sampling technique. In this study, 60 students were used as samples. The researcher used quantitative research. Then, the data were collected by a grammar test. The result of this research was that most students made errors in using noun phrase. There were 59 students made errors in determiner with 410 errors or 28,4%. The errors of pre-modifier were found in 60 students, with 603 errors or 40,2%. The errors of head was found in 52 students with 154 errors or 9,1%. The errors of post-modifier were found in 53 students with 117 errors or 39%. In conclusion, most of all students made noun phrase errors in determiner, pre-modifier, head, and post-modifier, with the dominant element error was pre-modifier with 40,2%.